PENGARUH SUPPORT GROUP THERAPY TERHADAP KEPATUHAN PENGOBATAN HIPERTENSI PADA LANSIA - Ilma Widiya Sari; Emy Kurniawati; Hana Rosiana Ulfah; Bambang Sudono Dwi Saputro (Jurnal Cakrawala Keperawatan, 2025)
Background: The disease most commonly suffered by the elderly is hypertension. Adherence to treatment for hypertensive people is important because hypertension is a disease that cannot be cured but must always be controlled. Support group therapy can help the elderly to share experiences with each other so that they can increase compliance with hypertension treatment. Objectives: This study aims to determine the effect of support group therapy on medication adherence in elderly people with hypertension. Method: This research uses quantitative research with pre experiment design, one group pre test and post test. This study used a sample of 38 respondents—bivariate analysis using Paired T-Test. Result: The results of bivariate analysis using the Paired T-Test obtained the value of Sig. (2-tailed) of 0.000 so that the p-value <0.05 it can be concluded that there is a significant difference before and after being given support group therapy. Conclusion: These results indicate a significant influence of support group therapy on the medication adherence of elderly people with hypertension.